The vertical and horizontal ridge Augmentation of the alveolar ridge in the jaws, a literature review (Latakia University Journal -Medical Sciences Series, 2023)
Dimensional variations in the alveolar ridge after extraction often negotiations on achieving adequate implant stability and placement of implants in the right prosthodontic positions. These circumstances request augmentation of the residual ridge to accomplish successful implant placement and long-term survival. Vertical Ridge Augmentation is accomplished using both hard and soft tissue grafting procedures that intend to augment the alveolar ridge volume beyond the existing skeletal envelope; they are usually performed at the edentulous site of a deficient alveolar ridge . Although there are a large variety of alveolar ridge augmentation techniques with various degrees of success, this review concentrate on vertical ridge augmentation using guided bone regeneration, autogenous block and alveolar distraction osteogenesis . Vertical ridge augmentation procedures before or during dental implant placement are technically challenging and often encounter procedure-related complications.. A decision tree based on the amount of additional ridge height Residual ( 6 mm) is developed to improve the procedure-selection process.